Особливості перебігу постпрандіального дистресс-синдрому у школярів - Пащенко, Ірина Володимирівна (RS Global Sp.z O.O. Warsaw, Poland, 2019)
Postprandial distress syndrome is a highly prevalent manifestation of functional gastrointestinal dyspepsia at children's and teenage age. It appears by the feeling of early satiety at consumption of food and slowed-down evacuation of stomach content, postprandial fullness in an epigastrium. The research objective is assessment of the peculiarities of postprandial distress syndrome progress at children of school age, and the choice of the best possible scheme of treatment. Under our observation there were 107 children aged from 7 up to 16 years with manifestations of postprandial distress syndrome. All school children had complaints of general character and dyspeptic manifestations, such as fatigue, headache, loss of appetite, nausea, eructation, feeling of overflow in epigastrium and gastric flatulence, periodic vomiting, tympanitis. Improper feeding, genetic predisposition to gastroduodenal pathology, prescripted repeated courses of antibacterial therapy, emotional stresses and associated nervous system diseases were trigger factors of postprandial distress syndrome progression. Rational treatment allowed to improve quality of life of children and to reach long remission.
Keywords: дитяча гастроентерологія; posprandial distress syndrom; functional dyspepsia; children